Infusion of autologous adipose tissue derived neuronal differentiated mesenchymal stem cells and hematopoietic stem cells in post-traumatic paraplegia offers a viable therapeutic approach - Umang G Thakkar; Aruna V Vanikar; Hargovind L Trivedi; Veena R Shah; Shruti D Dave; Satyajit B Dixit; Bharat B Tiwari; Harda H Shah (Advanced Biomedical Research, 2016)
Background: Spinal cord injury (SCI) is not likely to recover by current therapeutic modalities. Stem cell (SC) therapy (SCT) has promising results in regenerative medicine. We present our experience of co-infusion of autologous adipose tissue derived mesenchymal SC differentiated neuronal cells (N-Ad-MSC) and hematopoietic SCs (HSCs) in a set of patients with posttraumatic paraplegia. Materials and Methods: Ten patients with posttraumatic paraplegia of mean age 3.42 years were volunteered for SCT. Their mean age was 28 years, and they had variable associated complications. They were subjected to adipose tissue resection for in vitro generation of N-Ad-MSC and bone marrow aspiration for generation of HSC. Generated SCs were infused into the cerebrospinal fluid (CSF) below injury site in all patients. Results: Total mean quantum of SC infused was 4.04 ml with a mean nucleated cell count of 4.5 × 104/μL and mean CD34+ of 0.35%, CD45−/90+ and CD45−/73+ of 41.4%, and 10.04%, respectively. All of them expressed transcription factors beta-3 tubulin and glial fibrillary acid protein. No untoward effect of SCT was noted. Variable and sustained improvement in Hauser's index and American Spinal Injury Association score was noted in all patients over a mean follow-up of 2.95 years. Mean injury duration was 3.42 years against the period of approximately 1-year required for natural recovery, suggesting a positive role of SCs. Conclusion: Co-infusion of N-Ad-MSC and HSC in CSF is safe and viable therapeutic approach for SCIs.